2014
DOI: 10.1016/j.crohns.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for clinically actionable computed tomography findings in inflammatory bowel disease patients seen in the emergency department with acute gastrointestinal symptoms

Abstract: The yield for CAF with APCT in the ED was high for CD patients but minimal for those with UC and was not improved by the use of contrast. Elevated CRP, low BMI, Black race and previous history of IBD surgery predicted CAF in CD but no variables were predictive of CAF in UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 31 publications
2
34
2
Order By: Relevance
“…1,2,13,20 However, we found that almost 50% of patients had a clinically significant CT finding. This higher incidence is likely due to a more inclusive definition of what constitutes a CD-related CT finding (abscess, fistula, stricture, perforation, bowel obstruction), in addition to including non-CD related findings (i.e.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…1,2,13,20 However, we found that almost 50% of patients had a clinically significant CT finding. This higher incidence is likely due to a more inclusive definition of what constitutes a CD-related CT finding (abscess, fistula, stricture, perforation, bowel obstruction), in addition to including non-CD related findings (i.e.…”
Section: Discussionmentioning
confidence: 66%
“…Prior work has identified IBD related surgery, African American race, low body mass index (BMI), and C-reactive protein (CRP) as factors associated with clinically significant CT findings in patients with CD. 20 Two different predictive models have been developed to help clinicians determine the utility of ordering a CT scan. One model uses history of obstruction, history of abscess, presence of hematochezia, and WBC >12,000 to predict significant findings, whereas the other model uses erythrocyte sedimentation rate (ESR) and CRP.…”
Section: Introductionmentioning
confidence: 99%
“…The disadvantages of oral contrast include delays in diagnosis or surgical intervention and ED throughput, potentially increased radiation exposure because of dose modulation techniques currently used with many scanners and questionable added diagnostic benefit. 44,[52][53][54][55][56][57][58][59] Additionally, positive (bright) oral contrast may mask mucosal abnormalities associated with Crohn's disease. Hence, a CT with intravenous contrast but without oral contrast has become the standard in many institutions (Figures 1 and 2).…”
Section: Ctmentioning
confidence: 97%
“…However, Kerner et al 41 found that during an 8-year period, CT use in ED patients with Crohn's disease increased from 47% to 78% of encounters, with no change in admission rate (68% in 2001 versus 71% in 2009) and no change in yield of CT. And yet, data also suggest that the yield of CT in identifying obstruction, perforation, abscess, or other urgent noninflammatory-bowel-disease-related diagnoses is fairly high, ranging from 32.1% to 38.7% in ED-based studies. 41,42,44,45 In a Canadian study of 152 patients with Crohn's disease and 130 with ulcerative colitis presenting to an ED over a 2-year period, CT was performed for 49% of the Crohn's disease patients and 19% of the ulcerative colitis patients and was believed to change clinical management in 80% and 69% of encounters, respectively. 34 This was based on incompletely specified criteria but included disease requiring drainage, surgery, or other intervention.…”
Section: Imaging and Associated Radiation Exposure Among Patients Witmentioning
confidence: 99%
“…In a study from the United States, no significant findings were observed in 32.8% of CT imaging studies carried out in IBD patients in the ED [31] . Preliminary algorithms to avoid inappropriate use of CT imaging in IBD patients presenting to the ED have been proposed and require validation [31,32] .…”
Section: Ulcerative Colitismentioning
confidence: 99%